Situational Awareness: Inequity. - Weinstein, James (Spine, 2020)
... In this Covid19 pandemic the expedited scientific publishing process for some manuscripts has been subject to tarnished reviews allowing the national press to be a megaphone for misinformation .... The impact of misinformation effects all people but unfortunately some more than others. In a world stricken by the worst Pandemic since 1918, the worst recession since 1933, and the worst riots since the 1960s how can situational awareness help us move forward as a global society.